IMF Staff papers : Volume 39 No. 2. (IMF Staff Papers; IMF Staff Papers, 1992)
This paper answers key questions in considering a value-added tax (VAT) for Central and Eastern European countries. The paper emphasizes that in Western countries tax policy derives from the assumption that the market achieves an optimal allocation of resources. Efficiency in resource allocation and, by extension, the neutrality advantages of the VAT cannot be attained if prices continue to be controlled by the government and enterprises continue to be subject to undue regulation and direction from the center. If a VAT is not to resemble the kind of bookkeeping exercise of the old turnover taxes, then its introduction should be preceded by a substantial degree of price liberalization and enterprise autonomy. Finally, a VAT is a 'democratic tax,' in the sense that, in the main, taxpayers must comply voluntarily with the obligations imposed on them. Also, they have the right to disagree with the tax liability as ascertained by the tax office. This requires carefully crafted procedures and sustained efforts to elicit taxpayer cooperation.